Which Corporate ESG News Does the Market React To?. Issue 1 (2nd January 2022) - Serafeim, George; Yoon, Aaron
Abstract: We analyze 109, 014 firm–day observations for 3, 109 companies and examine market reaction to different ESG news. We find that prices react only to financially material ESG news, and the reaction is larger for news that is positive, receive more news coverage, and related to social capital issues. Using a prediction model based on pre-existing ESG ratings, we separate news into expected and unexpected components and find the market reacts to unexpected news. We conclude that investors are motivated by financial rather than nonpecuniary motive as they differentiate in their reactions based on whether the news is likely to affect fundamentals.